2016
DOI: 10.1370/afm.1967
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Psychological Interventions for Postnatal Depression in Primary Care: A Meta-Analysis

Abstract: PURPOSE Postnatal depression affects 10% to 15% of new mothers, and approximately 90% of cases are managed in primary care. Antidepressants are effective, but adherence is poor; therefore, psychological interventions must be investigated. In this systematic review, we assessed the efficacy of psychological therapies for postnatal depression in primary care. METHODSWe undertook a systematic search to identify articles published in English between 2000 and 2014 that reported studies meeting our eligibility crite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 54 publications
2
58
0
4
Order By: Relevance
“…Some studies have suggested that even when depressive symptoms are disclosed or recognized, many women fail to receive effective treatment. 21,22 Studies have shown that psychological interventions delivered in primary care are effective in reducing depressive symptomatology, [51][52][53] but in the UK at least, GPs report having few avenues to refer women for timely non-pharmacological treatment. 54 In our findings, antidepressant medication was the primary method of treatment in pregnancy, although there was some evidence that antidepressant medications were stopped during pregnancy, with few non-pharmacological alternatives being offered, which could lead to a significant risk of relapse.…”
Section: Effective Treatmentmentioning
confidence: 99%
“…Some studies have suggested that even when depressive symptoms are disclosed or recognized, many women fail to receive effective treatment. 21,22 Studies have shown that psychological interventions delivered in primary care are effective in reducing depressive symptomatology, [51][52][53] but in the UK at least, GPs report having few avenues to refer women for timely non-pharmacological treatment. 54 In our findings, antidepressant medication was the primary method of treatment in pregnancy, although there was some evidence that antidepressant medications were stopped during pregnancy, with few non-pharmacological alternatives being offered, which could lead to a significant risk of relapse.…”
Section: Effective Treatmentmentioning
confidence: 99%
“…A Cochrane review concluded that psychosocial and psychological interventions were effective in reducing depressive symptoms, at least in the short term. Although these interventions are perceived as acceptable to women, women with PPD still face barriers to engaging in such interventions. Barriers include traveling and child‐care practicalities, feelings of shame, and concerns about being judged as a mother and children being removed …”
Section: Introductionmentioning
confidence: 99%
“…Much attention has been paid to the problem of PPD in women, with meta‐analyses documenting PPD prevalence rates of 10%–15% (Gavin et al., ; Stephens, Ford, Paudyal, & Smith, ). As gender roles shift and paternal involvement in childcare becomes the norm, the experience of having a child requires major adjustments for men as well as women.…”
Section: Introductionmentioning
confidence: 99%